Prognostic Value Of Cardiac Biomarker And Electro Cardiography Of Canine Parvovirus-2 Affected Kanni Pups: A Study Of Eight Cases (Applied Biological Research, 2022)
Canine Parvovirus strains 2a, 2b, and 2c cause myocarditis and acute hemorrhagic gastroenteritis in  dogs (Goddard and Leisewitz, 2010). Severe clinical condition mostly affects puppies of < 6 months  ages while adult dogs with immunological deficiencies are also at danger (Mylokanis et al., 2016).  The enteritis variant of myocarditis is less prevalent than the myocarditis form. This type of  infection causes peracute mortality due to the heart failure in puppies infected during prenatal life  or in infants younger than 8 weeks age whose moms are not vaccinated. Cardiac biomarkers are  used as useful indicators for heart disease diagnosis. Such biomarkers include cardiac troponins  (cTnI, cTnT), creatine kinase myocardial band (CK-MB), and brain natriuretic peptide (BNP) (Er and Ok, 2015). Cardiac troponins are reliable indicators of cardiac damage, and even minor  elevations in these markers are significant in myocardial injury. In dogs with parvoviral enteritis  large increases in blood CK-MB and BNP levels, as well as a modest rise in cTnI levels have been  reported. Moreover, the evidences of hypercoagulability without disseminated intravascular coagulo pathy have been documented in puppies with CPV enteritis (Otto et al., 2000). In puppies with CPV  enteritis, hypercoagulability without disseminated intravascular coagulopathy has been observed  (Otto et al., 2000). Robinson et al. (1979) have reported that viral myocarditis suspected puppies  had small R waves, S-T segment elevation, QRS notching and paroxysmal ventricular tachycardia.  Only very young cardiac muscle fiber (in puppies of
Keywords: Prognostic Value; Cardiac Biomarker; Cardiography